Marketing and Post-Harvest Loss Assessment in Sapota - Gajanana, T M; Sudha, M; Dakshinamoorthy, V (Journal of Horticultural Sciences, 2006)
A study was undertaken in the Kolar district of Karnataka to assess the losses in post harvest handling and marketing of sapota. The analysis of data collected at the field level, market level, procurement centre of HOPCOMS and at the retail level indicated post harvest loss (PHL) of 15.98% in the wholesale marketing channel (WSM) and about 14.07 per cent in the HOPCOMS channel. Marketing system for sapota was found to be inefficient as the efficiency index was found to be less than 1. However, between WSM and HOPCOMS, the latter was found to be more efficient in terms of lower marketing cost, higher price realization by farmers and lower margin of the intermediaries. Use of mechanical harvester, pre harvest management of fruits against fruit borer and opening of procurement centres of HOPCOMS in the producing region are suggested in order to reduce the PHL and also to improve the efficiency of the marketing system.